Aberration in variation: deception by a CTA occult bleeding variant - Halim Lim, Aidi Aswadi; Md Ralib @ Md Raghib, Ahmad Razali; Shaharuddin, Nur Adilah; Shamsuddin Perisamy, Rajeev; Ahmad, Nur Fathihah (Lönge Medikal Sdn Bhd., 2022)
Introduction: The coeliac axis and its major branches are known to have various anatomical variations, some are more common than others. The presence of variants may complicate the upper abdominal procedures, such as open surgery or interventional radiology procedures. Result: This is a case of a 65-year-old gentleman with various co-morbidities, who initially presented with pyogenic spondylodiscitis. On day 7 of admission, he developed hypovolaemic shock secondary to upper gastrointestinal bleed, requiring massive transfusion protocol. An oesophago-gastroduodenoscopy (OGDS) revealed a Forrest 1b ulcer. Initially the bleeding stopped with endoclip application, but the haemorrhage subsequently resumed with further massive transfusion required. An abdominal CT angiogram (CTA) was then performed revealing active arterial extravasation at the site of the endoclip. However, the actual bleeding artery was not apparent. An aberrant right hepatic artery was observed on the CTA. A subsequent urgent embolization angiographic run revealed some contrast extravasation from the gastroduodenal artery, which arise from the common hepatic artery. 5 pieces of 0.035” coils were deployed at the bleeder site. No extravasation seen on the final angiographic run. However, the next day, the patient continued to developed massive haemorrhage. Another abdominal CTA demonstrated further similar extravasation of contrast near the endoclips. Another urgent embolization was then performed. Angiogram via the aberrant right hepatic artery revealed the presence of an accessory gastroduodenal artery, which in turn demonstrated sizable contrast extravasation near the endoclips. A microcatheter was used to deliver Histoacryl glue for embolization, which subsequently stemmed the bleeding. Conclusion: This case highlights the difficulty that arises during interventional procedure from the presence of anatomical variant of the coeliac axis. Although CTA is usually an important assessment tool prior to embolization, the accessory gastroduodenal artery was not opacified in the pre-embolization CTA. This underlines the need for an interventional radiologist to expect difficulty when variants are present